STRATEGI PEMERINTAH DALAM PENANGANAN GERAKAN SEPARATIS PAPUA DAN IMPLIKASINYA TERHADAP DIPLOMASI PERTAHANAN INDONESIA (GOVERNMENT STRATEGIES IN MANAGING PAPUA SEPARATIST MOVEMENT AND ITS IMPLICATIONS ON DEFENSE DIPLOMACY) - Mukhtadi, Mukhtadi (Jurnal Diplomasi Pertahanan, 2021)
This article discusses one of the government's efforts in handling the Papuan separatist movement. The Separatism Movement is a movement to gain sovereignty and separate from a territory or group of people from each other (or another country). In Papua, there is a group of people who want to be sovereign and break away from the Republic of Indonesia. A group of people called themselves Free Papua Organization (OPM). Papua de facto and de jure is one of the regions of Indonesia, so the Indonesian government prohibits anyone or any group that seeks to secede from the Republic of Indonesia (The Unitary State of The Republic of Indonesia). In Papua until now, there are still frequent conflicts related to political, economic, or socio-cultural issues. This research aims to find out how the government overcomes the separatist movement so that a group of people who call the OPM movement (Free Papua Organization) aware and return to the lap of the NKRI (Unitary State of the Republic of Indonesia)